The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/life12121964
|View full text |Cite
|
Sign up to set email alerts
|

Identifying MicroRNA Markers That Predict COVID-19 Severity Using Machine Learning Methods

Abstract: Individuals with the SARS-CoV-2 infection may experience a wide range of symptoms, from being asymptomatic to having a mild fever and cough to a severe respiratory impairment that results in death. MicroRNA (miRNA), which plays a role in the antiviral effects of SARS-CoV-2 infection, has the potential to be used as a novel marker to distinguish between patients who have various COVID-19 clinical severities. In the current study, the existing blood expression profiles reported in two previous studies were combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 114 publications
1
8
0
Order By: Relevance
“…Peripheral blood levels of miR-200c-3p have been suggested as potential biomarkers for IS ( 54 ). The reduced miR-34a-5p expression has been observed in lung tissues and airway samples of patients with COVID-19 ( 55 , 56 ). Increased miR-34a-5p expression induces brain cell apoptosis in patients with acute IS ( 57 ).…”
Section: Discussionmentioning
confidence: 97%
“…Peripheral blood levels of miR-200c-3p have been suggested as potential biomarkers for IS ( 54 ). The reduced miR-34a-5p expression has been observed in lung tissues and airway samples of patients with COVID-19 ( 55 , 56 ). Increased miR-34a-5p expression induces brain cell apoptosis in patients with acute IS ( 57 ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, miR‐320a had higher expression in OA chondrocytes and promote matrix degeneration 55 while a study conversely found that miR‐320a upregulated the expression of RUNX2 and inhibited OA cartilage degeneration 56 . Machine Learning predicted that miR‐24‐3p, targeting NRP‐1, significantly decreased in COVID‐19 patients 57 and could also inhibit S protein expression and SARS‐CoV‐2 replication 58 . As for OA, the chondrocyte destruction induced by IL‐1β was attenuated by miR‐24‐3p, 59 further indicating that miR‐24‐3p may alleviate the severity of both COVID‐19 and OA.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is essential and inevitable to provide efficient models for identifying and separating infected or suspected patients from healthy individuals. Within this short time since the first cases of the COVID-19 were reported, researchers have used MAs for its diagnosis and prevention with promising results [97][98][99]. These applications can be broken down into three categories: screening, prediction, and diagnosis [7,16].…”
Section: Application Of Bmcmbo Algorithm In Fs For the Covid-19 Diagn...mentioning
confidence: 99%